Habitual physical activity is not associated with lower cardiovascular risk profile or higher aerobic fitness - Valério, Denis Fabrício; Gáspari, Arthur Fernandes; Souza, Giovana Vergínea de; Libardi, Cleiton Augusto; Cavaglieri, Claudia Regina; Chacon-Mikahil, Mara Patrícia Traina (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Physical inactivity is considered as one of the factors to increase the risk of developing cardiovascular diseases (CVDs) and decrease aerobic fitness mainly in middle-age. Increased habitual physical activity (HPA) is one of the strategies recommended to reduce physical inactivity. However, it is not known whether middle-age individuals who exclusively perform greater amount of HPA have greater aerobic fitness and / or a lower risk of CVDs. Objective: Verify the association between HPA with the risk of CVDs and aerobic fitness in individuals who only perform HPA. Method: We selected 89 male volunteers, age: 47.4 ± 5.06 years, who did not practice systemized physical training. Our measurements were: HPA by the International Physical Activity Questionnaire and Baecke questionnaires, the aerobic fitness by direct assessment of maximal oxygen consumption (VO2 máx) and the risk of developing cardiovascular disease by the score calculation of General Cardiovascular Risk Profile from Framingham Study. Results: There was no correlation of the HPA level with cardiovascular risk factors, general cardiovascular disease risk and VO2 máx. Moreover, no difference was found between the categorical groups of the IPAQ questionnaire and between the groups, “clusters”, calculated from the Baecke questionnaire scores for the variables of cardiovascular risk, general cardiovascular disease risk and VO2 máx. Conclusion: This study have found that the HPA level of middle-aged men is not associated with lower cardiovascular risk profile or higher aerobic fitness, suggesting that only increase HPA may not be enough to promote beneficial adaptations in aerobic fitness and improve risk profile for CVDs. These results may be related to low volume and intensity of HPA, which reinforces the importance of performing physical training with control of these variables for health promotion.